Falla cardíaca con fracción de eyección preservada (2016)
ABSTRACT: Heart failure with preserved ejection fraction (EF) is defined as the presence of signs and symptoms of this disease with an EF ≥ 40 % and myocardial structural or functional impairment. Methodology: We followed the steps defined in the Methodological Guide for the Preparation of Clinical Practice Guidelines and Economic Evaluation in the General System of Social Security of the Colombian Ministry of Health and Social Protection, to develop clinical practice guidelines based on evidence (GPC). Results: In this issue we present the recommendations to treat heart failure with preserved ejection fraction. Conclusion: Advances in the treatment of heart failure with reduced ejection fraction have not shown a similar effect in patients with preserved EF. Specific recommendations for the treatment of these patients are established.